2020
DOI: 10.1021/acs.est.9b07540
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanoplastics in Alpine Snow: A New Method for Chemical Identification and (Semi)Quantification in the Nanogram Range

Abstract: We present a new method for chemical characterization of micro- and nanoplastics based on thermal desorption–proton transfer reaction–mass spectrometry. The detection limit for polystyrene (PS) obtained is <1 ng of the compound present in a sample, which results in 100 times better sensitivity than those of previously reported by other methods. This allows us to use small volumes of samples (1 mL) and to carry out experiments without a preconcentration step. Unique features in the high-resolution mass spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
174
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 26 publications
1
174
3
Order By: Relevance
“…Our findings indicate a new possible source and formation mechanism for AMP, different to those found for the terrestrial and coastal AMP detected to date 13,[22][23][24][25][26][27][28][29][30][31][32][33] . We have evidence from the open ocean, which suggest that AMP is emitted from the seawater into the atmosphere through wind related processes.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Our findings indicate a new possible source and formation mechanism for AMP, different to those found for the terrestrial and coastal AMP detected to date 13,[22][23][24][25][26][27][28][29][30][31][32][33] . We have evidence from the open ocean, which suggest that AMP is emitted from the seawater into the atmosphere through wind related processes.…”
Section: Resultscontrasting
confidence: 71%
“…We postulate that these results underestimate the actual AMP concentration in the marine atmosphere due to the current technical challenges, which did not allow us to analyze airborne microplastic particles smaller than 5 µm (see "Methods" section for more details). Moreover, nanoplastic particles (<1 µm) were only very recently identified in the environment at the single particle level 28 , due to methodological limitations in nanoplastic collection and detection 44,53 . In a typical marine aerosol size distribution, the diameter range between 10 nm-1 µm constitutes >99% of the total marine airborne particle concentration 52 , as was also measured during the R/V Tara Pacific expedition 38 (see Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the majority of the fibres was <25 μm size, these number concentrations can be converted to mass concentrations of 3.4 ± 2.8 and 3.6 ± 0.80 ng g −1 in Svalbard and Bavaria, respectively. Materić et al 65 reported PET (polyethylene terephthalate), PPC (polypropylene carbonate) and PVC (polyvinyl chloride) concentrations in Alpine snow of 5.6-23, 11-16 and 6.9 ± 0.2 ng g −1 , respectively. These concentrations are ~100 times higher than those estimated here for TWPs and BWPs in snow (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of the fibers was <25 μm size, these number concentrations can be converted to mass concentrations of 3.4±2.8 ng g -1 and 3.6±0.80 ng g -1 in Svalbard and Bavaria, respectively. Materic et al 51 reported PET, PPC and PVC concentrations in Alpine snow of 5.6-23 ng g -1 , 11-16 ng g -1 and 6.9±0.2 ng g -1 , respectively. These concentrations are about 100 times higher than those estimated here for TWPs and BWPs in snow (see Fig.…”
Section: Discussionmentioning
confidence: 99%